Sequential therapy in patients receiving Fluoroquinolones at the American University of Beirut Medical Center. (c2001) - Homsi, Maria (2001)
Availability of oral antibiotics with superior pharmacokinetic profiles and safety has enabled early conversion from parenteral to oral antibiotic therapy in attempt to reduce overall cost. In Lebanon, no hospital has set guidelines regarding switching from intravenous (IV) to oral (PO) antibiotics. The objective of this study was to evaluate such practice at a tertiary care medical center. Patients admitted to AUBMC, receiving intravenous ciprofloxacin, levofloxacin, or ofloxacin were enrolled prospectively. Variables were collected daily from admission until discharge, including antibiotics prescribed, vital signs, CBC, and cultures. Date of switch (if applicable), oral antibiotic chosen, mean time to switch, mean hospital duration, and mean treatment duration were also recorded. Patients were evaluated for appropriateness of switch according to set guidelines summarized from previously published data. 195 patients were divided into three groups depending on the quinolone prescribed. Patients were then divided into two groups: treatment and prophylaxis, in which there were 124 and 71 patients respectively. Only 54.8% were switched. 53.6% of patients not switched could have been eligible candidates for oral therapy. Mean time to switch was 4.7 days, 4.6 days, and 3.6 days for the ofloxacin, levofloxacin, and ciprofloxacin groups respectively. While the mean time to switch was similar in the three groups, ciprofloxacin patients had a slightly longer duration of treatment at home. Identification of hospitalized patients eligible for switch therapy should be a target for intervention to hospitals in effort to decrease cost.